Teaching Specialized Subjects in Foreign Languages at the Universities of Uzbekistan, Problems and Their Solutions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Objective: The research paper addresses the crucial necessity of preparing students as competent professionals capable of meeting the requirements of the modern world, with a focus on the essential role of mastering languages in this preparation. The primary goal is to pinpoint issues in teaching foreign languages in technical fields, offer practical solutions, and suggest effective language teaching methods for Uzbekistan universities.Methods: The study utilizes author's research, various theoretical frameworks, empirical studies, and practical insights, including in-depth analyses of cases, and group discussions to explore opinions and ideas. The practical experience and theories of famous scholars and linguists such as Cora Lindsay, Leila Ranta, Angela Hildyard, Nematov Khamid, and Alibek Rustamov have been scrutinized.Results: The challenges identified, such as insufficient language proficiency, result from the lack of language requirements in technical fields, inadequate language instruction hours, and a lack of motivation among technical students. Proposed solutions involve introducing language requirements for admission, increasing dedicated language instruction hours, and encouraging educators to become proficient in foreign languages. Additionally, it is recommended to implement the comprehensive integration of Suggestopedia, and Content and Language Integrated Learning (CLIL) methods across all universities as a holistic approach to overcoming language proficiency challenges.